2007
DOI: 10.1093/bja/ael302
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic effects of oxytocin given as i.v. bolus or infusion on women undergoing Caesarean section

Abstract: We recommend that bolus doses should be used with caution, and further studies should ascertain if oxytocin is equally effective in reducing blood loss when given at a slower rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
168
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(182 citation statements)
references
References 9 publications
9
168
1
4
Order By: Relevance
“…bolus. 28 Overall, symptoms were much less frequent compared with frequencies reported in previous studies. 1,4 Palmer et al 1 reported all complaints and, in the study by Moran et al, 4 patients were asked for symptoms per-operatively, which could explain differences besides the differences in doses and in the way the drug was administered.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…bolus. 28 Overall, symptoms were much less frequent compared with frequencies reported in previous studies. 1,4 Palmer et al 1 reported all complaints and, in the study by Moran et al, 4 patients were asked for symptoms per-operatively, which could explain differences besides the differences in doses and in the way the drug was administered.…”
Section: Discussionmentioning
confidence: 52%
“…Blood pressure and HR were measured with 2-minutes interval and the short-acting effect of oxytocin on haemodynamic variables may have been underestimated. 7,9,28 This could explain why the decrease in MAP was less pronounced compared with other studies. 5,7,28 The non-invasive method was chosen in order to encourage patients to agree to participate in the study.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It is unclear whether reducing the administered dose of carbetocin may further reduce the incidence of this unwanted effect; therefore, further studies are warranted. Furthermore, although it is well established that oxytocin given by infusion produces fewer hemodynamic effects than when given by bolus, 18 less is known about the method of administration of carbetocin. It remains unclear why the manufacturer has recommended administration of carbetocin as an intravenous bolus over one minute.…”
Section: Discussionmentioning
confidence: 99%
“…Slow boluses or infusions of oxytocin have shown to reduce the cardiovascular effects of this drug. 19 Similarly, current recommendations suggest a slow intravenous bolus of carbetocin over one minute. 9, A It is not clear how this one-minute time frame was determined.…”
Section: Discussionmentioning
confidence: 99%